High value triterpenic compounds from the outer barks of several Eucalyptus species cultivated in Brazil and in Portugal - Domingues, R. M. A.
The chemical composition of the lipophilic extracts of the inner and outer bark fractions of Eucalyptus grandis and Eucalyptus urograndis (E. grandis x Eucalyptus urophylla) cultivated in Brazil and Eucalyptus maidenii, cultivated in Portugal was studied by gas chromatography-mass spectrometry. The extracts were shown to be mainly composed of triterpenic compounds (along with mono and sesquiterpenes in E. maidenii) followed smaller amounts of fatty acids, fatty alcohols, and aromatic compounds. Triterpenic acids (mainly ursolic, betulinic and oleanolic acids), are particularly abundant in outer barks representing 5.2 g/kg, 5.7 g/kg and 9.3 g/kg in E. urograndis, E. grandis and E. maidenii outer barks, respectively. Although these compounds were found in considerably smaller amounts than those previously reported for Eucalyptus globulus, the total amounts of bark generated every year in South American pulp mills using E. urograndis and E. grandis, as well as the growth potential of E. maidenii plantations, the bark residues from these species are obvious candidates for the extraction of valuable triterpenic compounds. (C) 2010 Elsevier B.V. All rights reserved.